Various Problems Arise in Industrial Economics If Wage Rate Increases: A Study for Nonlinear Budget Constraint - Devajit Mohajan; Haradhan Kumar Mohajan (Law and Economy, 2023)
This study tries to discuss the economic effects of various inputs if the wage rate of a firm is increased. Cobb-Douglas production function, 6×6 bordered Hessian matrix, and 6×6 Jacobian are used here during the mathematical calculations to investigate economic predictions. Adjustment of various inputs and outputs in future production are essential for the profit maximization. Therefore, appropriate decisions can make the firm stronger to face the various challenges of the twenty first century. In the study profit maximization is considered with subject to the nonlinear budget constraint.